THE DIVORCED FAMILY:: A NEW PERSPECTIVE - Costa, Liana Fortunato (2012)
The present paper deals with the systemic study of thedivorced family and intends to better understand this family's interactionand competency. The study is related specifically to the system -divorcedmother and her daughters. We chose the Case Study Method, which webelieve as being the best way to study such a familiar configuration in itsentirety. We see the divorced family as a qualified structure in itself,whose competency is experienced differently from the one of marriedfamily. The results analysed qualitatively lead us to focus the divorced asnot being a troublesome structure, but as a system in transition towardthe effectiveness of changes.